2016
DOI: 10.1111/jan.12893
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for actions and omissions: a discourse analysis of student nurse accounts of responding to instances of poor care

Abstract: This study provides information about how students account for their actions and omissions in relation to the reporting of poor care. Findings suggest ways educators might increase reporting of concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 47 publications
(62 reference statements)
1
47
0
Order By: Relevance
“…It is suggested that the potential negative consequences of action are so great that inaction, or in this case non‐reporting of poor care, is the only reasonable course open to the witness, and moreover, this is the same inaction that most reasonable people would take under the same conditions. According to Ion, Smith, Moir, and Nimmo (), accounts of this type serve to protect the individual both from cognitive dissonance and from the potentially negative evaluations of others, which might be expected to occur by placing self before patient.…”
Section: Reporting Poor Care: How Do Witnesses Respond?mentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that the potential negative consequences of action are so great that inaction, or in this case non‐reporting of poor care, is the only reasonable course open to the witness, and moreover, this is the same inaction that most reasonable people would take under the same conditions. According to Ion, Smith, Moir, and Nimmo (), accounts of this type serve to protect the individual both from cognitive dissonance and from the potentially negative evaluations of others, which might be expected to occur by placing self before patient.…”
Section: Reporting Poor Care: How Do Witnesses Respond?mentioning
confidence: 99%
“…While this “it's difficult” stance seems to the dominant position, it has been questioned by some commentators. In their discourse analysis of student nurses’ accounts of actions and omissions in relation to reporting poor care, Ion, Smith, et al ()) suggested that credence be given to the idea that perhaps nurses who witness poor care and do not report it are opting to privilege self, in preference to protecting the patient by directly tackling instances of poor care. Arguing for the continued relevance of moral character and individual accountability, Darbyshire, Ralph, and Caudle () have also been critical of those who have tried to remove all responsibility from the individual in order to place it within a depersonalised system or situation.…”
Section: Reporting Poor Care: How Do Witnesses Respond?mentioning
confidence: 99%
See 1 more Smart Citation
“…In either case, students were careful to portray themselves in a positive light. [33,48] For example, to describe reported incidents, students cited personal factors, such as moral strength or professional commitment. [48] Conversely, to describe unreported incidents, students highlighted external factors that hindered their ability to report.…”
Section: Themesmentioning
confidence: 99%
“…[33,48] For example, to describe reported incidents, students cited personal factors, such as moral strength or professional commitment. [48] Conversely, to describe unreported incidents, students highlighted external factors that hindered their ability to report. [48] When describing witnessed incidents, students used three distinct narratives: experienced nurses as 'saving the day' due to their expertise; the 'silence' of the student and hospital staff in their lack of disclosure of errors to patients; and the unease that students feel when experts are observed making mistakes.…”
Section: Themesmentioning
confidence: 99%